2010
DOI: 10.1155/2010/426239
|View full text |Cite|
|
Sign up to set email alerts
|

Towards a Systems Approach in the Genetic Analysis of Archaea: Accelerating Mutant Construction and Phenotypic Analysis inHaloferax volcanii

Abstract: With the availability of a genome sequence and increasingly sophisticated genetic tools, Haloferax volcanii is becoming a model for both Archaea and halophiles. In order for H. volcanii to reach a status equivalent to Escherichia coli, Bacillus subtilis, or Saccharomyces cerevisiae, a gene knockout collection needs to be constructed in order to identify the archaeal essential gene set and enable systematic phenotype screens. A streamlined gene-deletion protocol adapted for potential automation was implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 66 publications
(71 reference statements)
0
57
0
Order By: Relevance
“…In the halophilic Archaea Haloferax volcanii, the kae1-bud32 (gene fusion) and cgi121 are essential, precluding a direct genetic test of their role in t 6 A biosynthesis, and deletion of pcc1 had only a small decrease (»16%) in total t 6 A content. 40,49 Confirmation that the KEOPS/EKC complex was responsible for t 6 A formation came with in vitro reconstitution experiments. It was shown that both the KEOPS/EKC complex from Pyrococcus abyssi (Kae1, Bud32, Pcc1, and Cgi121), reconstituted from the individual genes expressed in E. coli, as well as the S. cerevisiae KEOPS complex (Kae1, Bud32, Pcc1, Cgi121, and Gon7), genes expressed in E. coli as a synthetic operon, 50 can form t 6 A in vitro, when combined with Sua5 from yeast or Archaea.…”
Section: Archaea and Eukaryamentioning
confidence: 96%
“…In the halophilic Archaea Haloferax volcanii, the kae1-bud32 (gene fusion) and cgi121 are essential, precluding a direct genetic test of their role in t 6 A biosynthesis, and deletion of pcc1 had only a small decrease (»16%) in total t 6 A content. 40,49 Confirmation that the KEOPS/EKC complex was responsible for t 6 A formation came with in vitro reconstitution experiments. It was shown that both the KEOPS/EKC complex from Pyrococcus abyssi (Kae1, Bud32, Pcc1, and Cgi121), reconstituted from the individual genes expressed in E. coli, as well as the S. cerevisiae KEOPS complex (Kae1, Bud32, Pcc1, Cgi121, and Gon7), genes expressed in E. coli as a synthetic operon, 50 can form t 6 A in vitro, when combined with Sua5 from yeast or Archaea.…”
Section: Archaea and Eukaryamentioning
confidence: 96%
“…Plasmids used to delete the HVO_1958 and HVO_2299 genes were constructed as described previously [44]. Briefly, ~600 bp regions up- and downstream of HVO_1958 and HVO_2299 were PCR-amplified from purified genomic DNA using Phusion polymerase (NEB) and the oligonucleotides listed in Table S3 and then inserted using In-Fusion (Clontech) into pTA131, linearized by digestion with Eco RI and Xho I.…”
Section: Methodsmentioning
confidence: 99%
“…Agmatine appears to be the major accumulating polyamine in this order (Table S1 in Supplementary Material available online at http://dx.doi.org/10.1155/2016/7316725) [36, 40, 41]. Agmatine is the precursor of agmatidine, an essential modification of the anticodon wobble cytosine in archaeal tRNA Ile CAU [4244]. Agmatine is therefore an essential archaeal metabolite that can be either synthesized de novo or salvaged [42].…”
Section: Introductionmentioning
confidence: 99%
“…pIKB227, a pTA131 derivative used to disrupt trmY (HVO_1989) was produced as described previously (Blaby et al 2010) using oligonucleotide pairs HVO1989_N_IfKO_Fwd, HVO1989_N_IfKO_Rev, HVO1989_C_ IfKO_Fwd, and HVO1989_C_IfKO_Rev to amplify the regions upstream of and downstream from the target gene. Demethylated pIKB227 was prepared by passaging the plasmid through E. coli (INV110, Invitrogen) and was subsequently used in the pop-in/ pop-out procedure (Allers et al 2004) to delete trmY on the H. volcanii H26 chromosome.…”
Section: Plasmid and Deletion Strain Constructionmentioning
confidence: 99%